The influence of the maternal peer group (partner, friends, mothers' group, family) on mothers' attitudes to obesity-related behaviours of their children - Adrian J. Cameron; Emma Charlton; Adam Walsh; Kylie Hesketh; Karen Campbell (BMC, 2019)
Abstract Background Relationships with others can have an impact on the attitudes of new mums to the obesity-related behaviours of their children. The aim of this study was to understand the degree to which other new mums (from their mothers' group), friends, partners, and other family members have an influence on maternal attitudes to child feeding, physical activity and television viewing behaviours in order to more accurately target obesity prevention interventions. Methods In a retrospective cohort study design using data from the InFANT randomized controlled trial, first-time mothers (n = 307) from Melbourne, Australia were asked in 2012-13 how much of an influence their partner, friends, mothers' group and family were on their attitudes to their pre-school aged child's feeding, physical activity and television viewing behaviours. The level of influence was examined using chi-square tests, t-tests, and analysis of variance, stratified by maternal education, age and body weight. We also examined associations between the influence of others on maternal attitudes and actual behaviours including breastfeeding duration, age at introduction of solid food and time their child spent outside. Results Mothers rated partners as having the strongest influence on their attitudes toward all obesity-related behaviours. The percentage reporting partners as a major influence were 28.7% (95% CI 23.8,34.0), 33.1% (28.0, 38.6) and 24.2% (19.6, 29.3) for child feeding, physical activity and television viewing, respectively. More highly educated mothers rated social connections as more influential than less educated mothers. The influence of partners on attitudes toward child feeding was associated with longer breastfeeding duration. Conclusions Mothers rated partners as a powerful influence on their attitudes toward the obesity-related behaviours of their pre-school children, suggesting that partners could be an important target of obesity-prevention initiatives. Since less educated mothers reported peers and family as a much weaker influence on their attitudes to obesity-related behaviours than more educated mothers, equity should be taken into consideration when contemplating obesity-prevention interventions that target mothers' groups.